Faktor-Faktor Terkait Kepatuhan dalam Menjalani Pengobatan pada Penderita Hipertensi di Puskesmas Gerunggang Kota Pangkalpinang : Factors associated treatment adherence among hypertension patients at Gerunggang Health Centre in Pangkalpinang City - Hermaniati, Dwiana; Lana Sari; Zahriah, Zahriah (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2024)
Hypertension is a condition where systolic blood pressure ≥140 mmHg and diastolic blood pressure ≥90 mmHg. Hypertension had the highest patient visits in Pangkalpinang City in 2021. The Health Center in Pangkalpinang City had the highest number of hypertension visits in 2021, which is Gerunggang Health Center with 7,746 visits. The research objective was to know the factors related to medication adherence in patients with hypertension at the Gerunggang Public Health Center in Pangkalpinang City. The method used was analytic observational with a cross-sectional approach. Sampling used an accidental sampling technique. The research sample consisted of 96 respondents. The measuring instrument used is a questionnaire analyzed by univariate and bivariate using the chi-square test. The results showed that the factors of long-suffering from hypertension (p= 0.000), level of knowledge (p= 0.000), affordability of access to health services (p= 0.001), family support (p= 0.001), the role of health workers (p= 0.013), and motivation for treatment (p=0.000) was related to medication adherence in patients with hypertension. Factors of gender (p=0.540), education level (p=0.650), employment status (p=0.966), and health insurance participation (p=0.295) were not related to medication adherence in patients with hypertension. The findings of this study can offer valuable insights for Community Health Centers to mobilize PTM cadres and deliver education on the significance of adherence to medication for individuals with hypertension.